Implementation and Analysis on Color Theory Usage in Website User Interface to Develop Brand Image - Cindy Ariadi; D Deli (IJISTECH (International Journal of Information System and Technology), 2022)
Each technology has its own interface, in creating an interface, of course, there are several important things that need to be considered, such as layout, content, and color. Regarding the use of color, there is color theory in making interface designs. In this study, the author created an interface design using the ADDIE method and produced a new interface from a company website and then tested it on 5 respondents. The results obtained are that the new website interface design is more eye-pleasing and comfortable for users to access and gather information from the website.